Synthesis and characterization of manganese(II), cobalt(II), nickel(II), copper(II) and zinc(II) complexes with new Schiff base derived from 6,7-dimethyl-quinoxaline-2,3(1H,4H)-dione and thiosemicarbazide - Al-Jibouri, Mahmoud Najim; Hasun, Saad Mohammad (European Journal of Chemistry, 2015)
New transition metal complexes of quinoxaline-2,3-dione-thiosemicarbazone ligand were prepared and characterized by elemental analysis, 1H and 13C NMR spectroscopy. The ligand (LH) was obtained by the reaction of 6,7-dimethyl-quinoxaline-2,3(1H,4H)-dione with thiosemicarbazide. All the complexes are found to be monomer in nature and have tetrahedral geometry. The IR spectra data revealed that the new Schiff base behaved as monobasic tridentate ligand through deprotonation of thiol-SH group, oxygen atom of C=O of pyrazine moiety and nitrogen atom of azomethine -C=N- group. However, the molar conductivity measurements proved the neutral nature of all metal complexes in DMSO solution, as well as the magnetic moment measurements investigated the high spin properties of all complexes.